Influence of light environment on yield determinants and components in large olive hedgerows following mechanical pruning in the subtropics of the Southern Hemisphere - Cherbiy Hoffmann, Silvana Ursula (2012)
Olive cultivation has expanded considerably beyond the Mediterranean Basin to include new areas in the Southern Hemisphere. This study evaluated the response functions of yield determinants and components to photosynthetically active radiation (PAR) in a large olive hedgerow (cv. ‘Arbequina’) in subtropical Argentina, and assessed whether mechanical pruning altered these relationships. Mechanical pruning was applied at the end of the winter dormant period to the east side and top of hedgerows oriented North–South, while the other side was left unpruned. The PAR distribution and leaf density at different positions within the hedgerow were measured over the two subsequent growing seasons with inflorescence density, fruit set, fruit density, individual fruit dry weight, and oil content (%) being assessed the second growing season. Hedgerow size increased substantially during the first season, especially on the pruned side and top, reducing transmitted PAR in much of the canopy to less than 20% of full Sun incident PAR values above the orchard. The relationship between leaf density (and thus number of axillary buds) and PAR was bilinear for the canopy positions within the unpruned side with a threshold of about 15% of full Sun PAR, above which leaf density did not increase. No relationships between leaf density and PAR were found within the pruned side and top. In contrast, inflorescence density exhibited a threshold of 18% of PAR for canopy positions within both the pruned and unpruned sides, although no relationship was apparent for the pruned top. Neither fruit set nor yield component relationships with PAR were affected by pruning. Fruit set had a linear response to PAR for the observed range of PAR values within the hedgerow (approx. 0–50% of full Sun). Individual fruit dry weight and oil content (%) also showed linear responses to PAR. The results suggest that oil production in large olive hedgerows (height × width) is limited by low solar radiation within the canopy, and that substantial vegetative growth triggered by mechanical pruning may be an important contributor to this limitation under current management practices in subtropical climates.